2019
DOI: 10.3390/medicina55100693
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High-Flow Nasal Cannula on the Outcome of Immunocompromised Patients with Acute Respiratory Failure: A Systematic Review and Meta-Analysis

Abstract: Background and objectives: High-flow nasal cannula (HFNC) can be used as a respiratory support strategy for patients with acute respiratory failure (ARF). However, no clear evidence exists to support or oppose HFNC use in immunocompromised patients. Thus, this meta-analysis aims to assess the effects of HFNC, compared to conventional oxygen therapy (COT) and noninvasive ventilation (NIV), on the outcomes in immunocompromised patients with ARF. The Pubmed, Embase and Cochrane databases were searched up to Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Full-text review of 38 potentially eligible studies identified 20 eligible studies. Of these, 17 were systematic reviews (SRs) 15,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and three were RCTs [41][42][43] (Fig. 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Full-text review of 38 potentially eligible studies identified 20 eligible studies. Of these, 17 were systematic reviews (SRs) 15,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and three were RCTs [41][42][43] (Fig. 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…A 2017 post hoc analysis found no difference in intubation rate or 28 day mortality between HFNC and conventional oxygen therapies [ 72 ]. Finally, meta-analyses of these studies comparing HFNC and conventional oxygen therapy or NIPPV demonstrate reduced intubation (RR 0.83–0.89), but no difference in mortality or length of stay [ [73] , [74] , [75] ]. HFNC is recommended over conventional oxygen therapies in this patient population and can reduce need for intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Successively, other studies have outlined the usefulness of HFNC in managing ARF in immuodepressed patients. 59,60 One recent meta-analysis by Cheng et al showed the superiority of HFNC versus COT in reducing the intubation rate, without benefit on survival. 60 Another meta-analysis confirmed the superiority of HFNC versus NIV in reducing the intubation rate, again without effect on mortality in the ICU.…”
Section: Current Clinical Applications Of Hfnc Oxygen Therapymentioning
confidence: 99%
“…59,60 One recent meta-analysis by Cheng et al showed the superiority of HFNC versus COT in reducing the intubation rate, without benefit on survival. 60 Another meta-analysis confirmed the superiority of HFNC versus NIV in reducing the intubation rate, again without effect on mortality in the ICU. 59 Other studies failed to show advantages of HFNC over standard treatment.…”
Section: Current Clinical Applications Of Hfnc Oxygen Therapymentioning
confidence: 99%